SOSIALISASI METODE PEMBELAJARAN YANG DAPAT MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI KELOMPOK B - Hariani Fitrianti; Muh. Rafi’y; Beatus Tambaip (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
Fine motor development in early childhood has not become a significant indicator in the development process of early childhood. This is due to a lack of knowledge from parents and teachers at PAUD institutions. appropriate learning methods are needed in the learning process. This service aims to make AUD teachers know what learning methods can be used in the process of developing their fine motor skills. This PKM was held at YAPIS Merauke Kindergarten and was attended by 11 YAPIS Merauke Kindergarten teachers. This activity was carried out in 4 sessions where each session using the lecture method and question-and-answer discussion. The results of this training are 1) an increase in teachers understanding of various learning methods that can improve AUD's fine motor skills. 2) increased creativity and innovation of teachers in designing appropriate learning methods according to the needs of early childhood group B. Furthermore, teachers are expected to be able to create more varied learning methods to support early childhood development